PENAPISAN GENOTIPE KAKAO TAHAN PENYAKIT BUSUK BUAH (Phytopthora palmivora) DI ACEH BESAR - Siti Hafsah; Zuyasna Zuyasna; Firdaus Firdaus (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
Screening genotypes of Aceh cacao to obtain resistant genotypes to Black Pod Disease (Phytopthora palmivora) is a key step. This study was conducted on basis of screening natural infection in the field and artificial infection in laboratory. The research was conducted in the field (Saree Aceh and East Aceh) and in the Plant Pathology Laboratory, Agriculture Faculty, Syiah Kuala University. The study started from March to November 2013. Results from the field and laboratory, based on artificial inoculation, showed that three genotypes originated from Saree Aceh i.e. SR 26, SR 40 and SR7 were resistant, indicated by the characters of long incubation period (more than five days), a small diameter of spot, slow growth of the spot, and low percentage of symptoms. The three genotypes had both a good wounded post-penetration and unwounded pre-penetration resistance. Conversely, cacao genotypes originated from East Aceh did not show a significant difference of post-penetration resistance.